Employer‐oriented labour market policies in Sweden: Creating jobs and the division of labour in the public sector. (29th April 2019) - Castillo, Daniel
Abstract : In many European countries, greater importance is accorded to labour market policies in which employers are involved in activating unemployed people. Such employer‐oriented policies target employers' demand for labour and attempt to influence their willingness to hire, train or guide (often disadvantaged) unemployed groups. Using data from a qualitative interview study of an employer‐oriented programme in a medium‐size city in Sweden, the present article aims to develop knowledge about how these policies are used to influence employers to hire unemployed workers and how jobs created in this context differ from regular jobs. The article argues that creating jobs through new arrangements for the division of labour, with the promise of relieving regular staff of unskilled tasks, may influence employers' willingness to hire the unemployed when used alongside other kinds of policy instruments. However, the article also shows that this new division of labour, with programme participants performing mainly unskilled tasks, has been difficult to realize, as new staff gradually come to perform an increasing number of regular working tasks.